2020
DOI: 10.1108/ijppm-06-2019-0293
|View full text |Cite
|
Sign up to set email alerts
|

Reverse supply chain management in manufacturing industry: a systematic review

Abstract: PurposeIn a quest to meet increasing pressure to incorporate environmental and sustainability factors due to the legislations and growing public awareness, companies are rethinking of strategizing their supply chain network to take control of the reverse flow of products as well. This growing interest has also led to tremendous growth in publications occurring in several reputed journals in the last few years. In this context, the purpose of this article is to perform a systematic literature survey of recent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 197 publications
(188 reference statements)
0
18
0
Order By: Relevance
“…The manufacturing industry was the focus of the literature review developed by Mathiyazhagan et al (2020). Dev et al (2020) suggested a study for sustainable reverse supply chain/logistics by employing the CE concept.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The manufacturing industry was the focus of the literature review developed by Mathiyazhagan et al (2020). Dev et al (2020) suggested a study for sustainable reverse supply chain/logistics by employing the CE concept.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Carter and Ellram (1998) [22], the definition of reversible logistics is: "The process by which companies can become more environmentally efficient by recycling, reusing, and reducing the amount of materials used".…”
Section: Reverse Logistics and Search Strategymentioning
confidence: 99%
“…However, textile recycling remains limited due to the sector's many socioeconomic challenges. The CE is the method of converting supply chain (SC) operations from a linear to a circular production/business model, through which used/waste materials and components are reintroduced by the SC through a closed-loop system by reusing, recycling, remanufacturing, reconstruction, and refurbishing as a way of recapturing inventory and reducing negative impacts [70,71]. With the adoption of CE strategies, waste generation from manufacturing can be reduced by a significant amount, (1) as well as CE implementation barriers to the creation of innovative sustainable business models.…”
Section: Ce In the Textile Sectormentioning
confidence: 99%